2017
DOI: 10.1016/j.enconman.2016.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal carbonization (HTC) of loblolly pine using a continuous, reactive twin-screw extruder

Abstract: Hydrothermal carbonization (HTC) has become an accepted means of converting a wide variety of lignocellulosic feedstocks into solid hydrochars, which have improved physical and chemical properties compared to raw biomass. To date, HTC applications have involved batch or semicontinuous process systems, which has limited their economic viability. The work presented here describes a fully-continuous HTC process, made possible by use of a specially modified twinscrew extruder (TSE). The reaction time within this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…Table 3 reports the results of the ICP analyses performed on the HTC liquid produced processing grape seeds, grape skins and grape marc respectively. The value of 8-13% of C in the aqueous phase for experiments with seeds is in agreement with literature [37,40]. At 180 • C, it seems to be clear that the carbon content decreases in the liquid phase for HTC experiments with seeds.…”
Section: Liquid Productssupporting
confidence: 91%
See 1 more Smart Citation
“…Table 3 reports the results of the ICP analyses performed on the HTC liquid produced processing grape seeds, grape skins and grape marc respectively. The value of 8-13% of C in the aqueous phase for experiments with seeds is in agreement with literature [37,40]. At 180 • C, it seems to be clear that the carbon content decreases in the liquid phase for HTC experiments with seeds.…”
Section: Liquid Productssupporting
confidence: 91%
“…When predicting the solid mass yields of the hydrochars for the three substrates with the trend lines, the absolute errors range between 0.02 and 9.39%, while the predictions for both the liquid and the gaseous phases seems to be less accurate in some cases, presenting absolute errors higher than 10%. Hoekman et al [40] proposed a different severity factor (hereinafter SFR0) shown in Equation 3, where t is expressed in min and T in • C, and applied it to hydrothermally carbonized loblolly pine:…”
Section: Yields Prediction Using a Severity Factormentioning
confidence: 99%
“…This severity factor equation has been used by other researchers for describing the HTC process as applied to various biomass feedstocks. For example, Gao et al [17] analysed the effect of water to biomass ratio on the HC yield of HTC of corn stalk and longan shell, and Hoekman et al [18] studied the HTC of loblolly pine in a continuous, reactive twin-screw extruder. Janga et al [19] applied a more complex severity model for the prediction of the monosaccharide yield via hydrolysis of different wood by concentrated sulfuric acid.…”
Section: Basic Kinetic Modelsmentioning
confidence: 99%
“…Although most publications in the hydrothermal field still discuss laboratory results, several pilot facilities and continuous process alternatives have recently been reported. [26] Hyperspectral imaging can be performed next to ap roduction line potentially allowing real-time process monitoring and control. In principle, images can also be recorded to the level of af ew microns after which the wavelengthi tself restricts furtheri ncreases in image detail.…”
Section: Discussionmentioning
confidence: 99%